Casper's haunted Christmas [videorecording (DVD)] - Buckley, Robert; Travis, Randy; Hurley, Owen (Universal, 2000)
Casper, The Friendly Ghost, is home for the holidays in this all-new, computer-animated, feature-length adventure that has fun and laughter all wrapped up in one spooktacular package.